Study of guangzhou house price bubble based on state‐space model - Hui, Eddie Chi Man; Gu, Qi (International Journal of Strategic Property Management, 2009)
Previous literature has explored Guangzhou's real estate market bubble problem, by using the perspective of rent receipts to measure the fundamental housing value. Since there is high proportion of owner‐occupied property in Guangzhou; and that the household income is considered a key factor affecting housing price level, this article is from the perspective of household income, by the present asset market model, it sets up housing price model that analysis of the bubble phenomenon, and uses the state‐space model that can be estimated characteristics by unobservable variables. The article estimates the price bubble and analyzes the size of the bubble at different times. The housing price in Guangzhou from January 2004 to December 2008 is studied. The results concluded that the housing market bubble peaked in October 2007 at around 43% of the market housing price.First Publish Online: 18 Oct 2010